STATUS, PROBLEMS AND PERSPECTIVES OF WORK OF ENTERPRISES IN UKRAINE - VLASENKO, Ivan; MYKHALCHYSHYNA, Larysa; BONDAR, Tetyana (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The successful operation of Ukrainian business enterprises is an important source of filling the state budget and creating jobs. During 2018-2021, the total number of operating enterprises as well as the number of employees increased slightly. Accordingly, the total volume of sold products, goods and services increased. Significant changes in the work of enterprises of all kinds took place with the beginning of a full-scale war. In order to stay on the market, companies are forced to significantly revise their expenses, including staff maintenance and the search for employees. The most widespread ways of optimization were transferring employees to half the rate, reducing the number of working hours or taking vacation at their own expense, and reducing wages. Many companies are forced to work in conditions of significantly lower incomes than before the war. Since they cannot transfer workers to reduced working hours due to the necessity of ensuring production, wages are reduced. In large companies, the situation is better than in small and medium-sized businesses, but there are no more job vacancies. The number of vacancies depends on consumer demand, and after the start of the war, Ukrainians significantly reduced their spending. This has had the greatest impact on traditionally low-income regions. The large gap between supply and demand in the market will remain for a long time, and this situation will continue even after the war. Ukrainians faced a big problem: lack of work and growing competition. The most demanded labor specialties now. Demand for such workers will increase as more and more companies resume operations. After the end of the war, the highest rates of growth will be achieved in industries that will work to restore the domestic market. At the first stage, construction, agriculture, food production, wholesale and retail trade, logistics, production of chemical products, electrical equipment, and furniture will develop most actively and require personnel. However, the need for professions will depend on Ukraine’s economic strategy. As part of the post-war recovery, it is worth emphasizing the creation of added value in well-developed industries. After the war, the labor market will depend on how actively the economy will be rebuilt and developed. This will also affect how many Ukrainians will return to the country. Here it is important not to repeat the mistakes of other countries. The main reason is the systemic flaws of the post-war reconstruction plans, which did not provide for large-scale measures to restart the production sector and restore industry.